Searching for truth - Draper, George Otis (Eckler, 1902)
Preface -- A well-meant warning -- The ever constant influence -- Christianity on the defensive -- The older doctrine -- The final tests -- Was Christ divine -- Christian morality -- The impracticability of Christianity -- The new sphere of effort -- Natural sources of the supernatural -- Possibilities of a future existence -- Logical morality -- Individual improvement -- General improvement -- Conclusions -- Appendix.